Assisted fertilization with own oocytes in women over 40 years of age: indications and results - Seminario Agurto, Jaime (2023)
Women postpone motherhood because of their desire for personal and professionalimprovement. It is known that the quantity and quality of oocytes per cycle dependson the patient’s age. Success rates in assisted reproduction treatments decreasewith age, especially after 40 years of age. Higher live birth rates are observed inyounger women, and rates decrease significantly in older women due to decreasedfertility and increased miscarriages. Therefore, age is crucial when assessing thepossibility of a successful pregnancy through assisted reproductive treatments(ART). The indications to perform in vitro fertilization (IVF) with own ovules in womenolder than 40 years include starting as soon as possible highly complex procedures,good evaluation of ovarian reserve with antimüllerian hormone analysis (AMH) andantral follicle count (AFC) for genetic counseling, proposing IVF-intracytoplasmaticsperm injection (ICSI) before the age of 44 years, generating realistic expectationsand informed consent, with own statistics. At REDLARA, of all IVF-ICSI procedures,34% of patients are over 40 years old; preference is given to transfer blastocystswith preimplantation genetic testing for aneuploidy (PGT-A) to select euploidembryos. Success rates are low, even when they are pregnancy rates per embryotransfer in the group of women ≥ 40 years (18.2% without PGT, 42.7% with PGT inIMRCRP). It is recommended to bank ovules or embryos by performing multipleovarian stimulations. A single embryo transfer should be chosen to avoid obstetriccomplications with multiple pregnancies in patients ≥40 years, because of the highrisk due to age.